Developing the creative spark: Identifying factors that facilitate innovation. Issue 5 (8th April 2014) - Unknown
Abstract : Purpose: – The purpose of this paper is to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds his own impartial comments and places the articles in context. Findings: – A broader approach to innovation is recommended, and firms should encourage employees at all levels to participate. Organizational structure impacts on creative output. An emphasis on collaboration has a positive effect, while hierarchical structures impede idea generation and execution. Employee perceptions of their workplace environment with regard to pressure and support from leaders and colleagues are also significant. There is potential for gender differences in the way such factors influence creativity. Practical implications: – This study provides strategic insights and practical thinking that have influenced some of the world's leading organizations.What is original/value of paper?: The briefing saves busy executives and researchers' hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and an easy-to digest format.